2022
DOI: 10.3389/fnbeh.2022.964348
|View full text |Cite
|
Sign up to set email alerts
|

Exploring decision-making strategies in the Iowa gambling task and rat gambling task

Abstract: Decision-making requires that individuals perceive the probabilities and risks associated with different options. Experimental human and animal laboratory testing provide complimentary insights on the psychobiological underpinnings of decision-making. The Iowa gambling task (IGT) is a widely used instrument that assesses decision-making under uncertainty and risk. In the task participants are faced with a choice conflict between cards with varying monetary reinforcer/loss contingencies. The rat gambling task (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Hence valuation, i.e. how mice assign a value to options, remains fundamentally subjective 57,58 . Computational models of decision-making constitute powerful tools designed to infer subjective valuation from the temporal series of choices.…”
Section: Discussionmentioning
confidence: 99%
“…Hence valuation, i.e. how mice assign a value to options, remains fundamentally subjective 57,58 . Computational models of decision-making constitute powerful tools designed to infer subjective valuation from the temporal series of choices.…”
Section: Discussionmentioning
confidence: 99%
“…In DM situations that require judgment based on experience and accumulated knowledge, as is the case of SDM, older adults perform as efficiently as the younger ones. 34,35 On the contrary, when the decision situation requires skills that decrease with age (such as working memory), older adults tend to perform DM tasks less efficiently. 36 Studies on age-related differences conducted using SDM tasks have shown that older people tend to exhibit more prosocial behaviors than younger individuals, which is in agreement with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…After completing the forced-choice training, rats performed the rGT task (i.e., with all the options presented simultaneously) during 25 sessions to establish a stable response at baseline. A choice score [(%P1+%P2)–(%P3+%P4)] was used as an index of RDM ( Zeeb and Winstanley, 2013 ; Fugariu et al, 2020 ; Hultman et al, 2022 ), with a lower choice score indicating less optimal decision-making. Impulsive action was defined as the percentage of premature responses performed during the ITI (i.e., number of premature responses/total number of trials initiated × 100; Ferland and Winstanley, 2017 ).…”
Section: Methodsmentioning
confidence: 99%